Accuracy of digital impressions versus conventional impressions for 2 implants: an in vitro study evaluating the effect of implant angulation - Jaafar Abduo; Joseph E. A. Palamara (SpringerOpen, 2021)
Abstract Background Accurate implant impression is an essential requirement for the fabrication of implant prosthesis. This in vitro study evaluated the accuracy of digital impressions by intraoral scanner (IOS) systems in comparison to conventional impressions for recording the position of 2 parallel implants and 2 divergent implants. Materials and methods In vitro 3-unit prosthesis master models with 2 tissue level implants were fabricated; one model had parallel implants, and the other model had one 15° tilted implant. The conventional open-tray impressions were obtained with non-splinted (NSP) and splinted (SP) impression copings. Trios 4 (TS), Medit i500 (MT), and True Definition (TD) were used to make digital impressions with scan bodies. A total of 10 impressions were obtained with every technique. The virtual test images of the conventional and digital impressions were converted to 2 virtual implant images. For each group, trueness, precision, inter-implant distance deviation, and angle deviation were measured. Results There was a general tendency for digital impressions to provide a more accurate outcome for trueness, precision, and angle deviation. The 2 conventional impressions showed similar accuracy, except for the angle deviation, where the NSP was significantly inferior than SP (p < 0.01) for the divergent implants model. The TD was generally the least accurate among all the IOS systems, especially for the inter-implant distance deviation (p < 0.05). Conclusions Within the limitations of the laboratory set-up of the present study and the limited clinical resemblance, the digital impressions appeared to have sufficient accuracy for 2 implants and were least affected by the presence of angle between implants. The most inferior outcome was observed for the NSP technique.